The use of environmentally friendly means of protection in pea agrocenoses for the production of organic products - Vlasova, О.; Sekun, M.; Zatserklyana, M. (Quarantine and plant protection, 2021)
Goal. Substantiate the use of environmentally friendly means of protecting peas with modern technologies of crop cultivation. Methods. Field, laboratory, mathematical-statistical, calculation. Results. The relationship between the spread of diseases and the main environmental factors (temperature and humidity, atmospheric precipitation) during the growing season of plants has been investigated. The terms and norms of processing with biological products and their effectiveness have been established. Methodological recommendations have been developed for the use of environmentally friendly means of protection, which are based on the use of biological preparations in pea agrocenoses and in the production of organic products. Conclusions. In agrocenoses of peas, the use of biological plant protection products for the production of organic products is recommended.